2022
DOI: 10.1136/bmjopen-2021-057850
|View full text |Cite
|
Sign up to set email alerts
|

Achievement rate and predictive factors of the recommended therapeutical target in patients with axial spondyloarthritis who remain on biological therapy: a prospective cohort study in Spain

Abstract: ObjectivesTo determine the frequency of sustained remission (R) or low diseas activity (LDA) in patients with axial spondyloarthritis (axSpA) undergoing long-term biological therapy and to analyse predictive factors for achieving these outcomes.DesignProspective, observational cohort study.SettingSpanish hospital.ParticipantsPatients with axSpA who initiated biological treatment between 2003 and 2017.InterventionAssessment of demographic and clinical characteristics at the beginning of treatment and disease ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For example, in a Spanish prospective cohort, one-third of patients on biological therapy for axSpA achieved a low activity status over 18 months, and less than 20% achieved remission. 5 In a report from the Scandinavian registries, analysis of targeted therapy switches in more than 6000 patients revealed that 8%, 3% and 1% of patients received at least three, four or five targeted therapies, respectively, during the 3 years of follow-up. There was no relationship between the number of rotations and calendar period.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…For example, in a Spanish prospective cohort, one-third of patients on biological therapy for axSpA achieved a low activity status over 18 months, and less than 20% achieved remission. 5 In a report from the Scandinavian registries, analysis of targeted therapy switches in more than 6000 patients revealed that 8%, 3% and 1% of patients received at least three, four or five targeted therapies, respectively, during the 3 years of follow-up. There was no relationship between the number of rotations and calendar period.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…Axial spondyloarthritis patients with positive HLA-B27 status seem to respond better to therapy. In a Spanish prospective observational cohort of 186 axSpA patients who initiated biological treatment between 2003 and 2017, HLA-B27 positive status was associated with achieving a state of remission or low disease activity (OR 4.30 95% CI 1.68–11.01) [91 ▪ ].…”
Section: Human Leucocyte Antigen-b27 and Response To Treatmentmentioning
confidence: 99%
“…The implementation of biological disease-modifying anti-rheumatic drugs (bDMARDs) has also revolutionized the pharmacological treatment options, when non-steroidal anti-inflammatory drugs (NSAID) and physiotherapy are not sufficient. Nevertheless, maintained remission over time is uncommon [ 3 ], and a large proportion of patients with r-axSpA still experience residual pain, stiffness, a deteriorated physical capacity, and reduced health-related quality of life [ 4 ]. Patients with SpA themselves often experiment with different dietary regimens in the hope of alleviating their symptoms or to reach prolonged remission [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%